Healing leaves - Luteran, Paula (Kansas State University, 2011)
Medieval French literature provides the modern researcher with references to the healing arts in many passages that are incorporated into prose or poetic works. Because there was no clear separation of the genres into modern classifications, references to treatment of sicknesses of body, mind or spirit are woven into many literary works, providing us with a kind of snapshot of the state of the art healing practices of the day. Texts make reference to herbs and plants used to cure the ailments of the body, gardens and flowers that refresh the spirit, miraculous unguents, cures through the intercession of the saints and the Virgin Mary and surgical procedures. Texts examined here include Le Roman de la Rose, Erec et Enide, Aucassin et Nicolette, Les Lais of Marie de France, Le conte du Graal, Le chevalier de la charrette, La Condamnation de Banquet, Yvain, Cligès, La Chanson de Roland and Treize Miracles de Notre-Dame. The picture they provide of the medicine of the time has a certain charm and quaintness that many moderns seek in holistic treatments of today which hearken back to this more rustic medicine.
Keywords: Medieval French Literature; Medieval Medicine; Spring; Language, Modern (0291)